Insights from the Den: How Hibernating Bears May Help Us Understand and Treat Human Disease. Issue 5 (17th June 2015) - Berg von Linde, Maria; Arevström, Lilith; Fröbert, Ole
Abstract: Hibernating brown bears ( Ursus arctos ) and black bears ( Ursus americanus ) spend half of the year in a physically inactive state inside their winter dens without food intake and defecating and no or little urination. Under similar extreme conditions, humans would suffer from loss of lean body mass, heart failure, thrombosis, azotemia, osteoporosis, and more. However, bears exit the den in the spring strong without organ injuries. Translational animal models are used in human medicine but traditional experimental animals have several shortcomings; thus, we believe that it is time to systematically explore new models. In this review paper, we describe physiological adaptations of hibernating bears and how similar adaptations in humans could theoretically alleviate medical conditions. The bear has solved most of the health challenges faced by humans, including heart and kidney disease, atherosclerosis and thrombosis, and muscle wasting and osteoporosis. Understanding and applying this library of information could lead to a number of major discoveries that could have implications for the understanding and treatment of human disease.